A New Chiral Ni4O4 Distorted Cube: Synthesis, Structure, and Magneto‐Structural Correlation. Issue 34 (29th August 2019) - Sen, Rupam; Lopes, Armandina M. L.; Lin, Zhi; Brandão, Paula; Araújo, Joao P.
Abstract : A new chiral tetranuclear Ni4 O4 complex has been developed with distorted cubane‐type structure. The structure was determined by single‐crystal X‐ray diffraction. The new tetradentate Schiff‐base ligand in this compound was synthesized via the condensation of 2′‐hydroxyacetophenone and ( R )‐3‐amino‐1, 2‐propanediol. Temperature dependent magnetization measurements showed a predominant ferromagnetic interaction among the four Ni centers. The best fit of the χT vs. T curve results in a solution with two exchange interaction values, J 1 =12.7 cm –1, and J 2 =1.6 cm –1 which are appreciably correlated with the structure. Ac susceptibility data were collected between 2 and 28 K and it is found that the data display a small frequency dependence with the peaks shifting to higher temperatures with increasing frequencies. Abstract : A new polynuclear chiral magnetic complex has been synthesized. In the compound four nickel centers are connected with each other by the chiral bridging ligand. The low temperature magnetic studies reveal the presence of ferromagnetic interaction among the metal centers.